Effect of catalyst concentrations on the growth of carbon nanotubes from waste engine oil - - S.Alfarisa, - R.N. Safitri, - W.S.B. Dwandaru, (Universiti Pendidikan Sultan Idris, 2016)
Effect of catalyst concentrations on the growth of carbon nanotubes from waste engine oil by - S.Alfarisa, - R.N. Safitri, - W.S.B. Dwandaru,